674 The importance of Alpha-1 Antitrypsin (AAT) and respiratory rehabilitation in patients with lung diseases (Balneo and PRM Research Journal, 2024)
Background: The incidence of lung diseases is very high worldwide, especially in the case of lung cancer, pulmonary tuberculosis, and obstructive ventilatory dysfunctions. Alpha-1 antitrypsin (AAT) is synthesized mainly by hepatocytes, and one of its roles is to inhibit protease activity in the body's biological fluids following the phenomenon of programmed cell death, which is also called apoptosis. Acute lung diseases, but especially chronic ones, can cause, in addition to pulmonary and extrapulmonary manifestations, social and psychological impact, which is why a complex, interdisciplinary respiratory rehabilitation program is necessary. Objectives: Our study aimed to determine the correlation between alpha-1 antitrypsin values and lung diseases (pulmonary tuberculosis, lung cancer, asthma, and COPD) and to evaluate the influence of the individualized respiratory rehabilitation program in these diseases. Methods: We carried out a retrospective study between February 2022 and March 2023 in the Pneumology Department of the "Victor Babeș" Clinical Hospital of Infectious Diseases and Pneumoftiziology, Craiova. It included 189 patients diagnosed with pulmonary tuberculosis, lung cancer, or obstructive ventilatory dysfunctions (chronic obstructive pulmonary disease – COPD or asthma). Alpha-1 antitrypsin was collected from all patients. Respiratory rehabilitation was carried out both during hospitalization and in an out-patient setting for a maximum period of 6 months after discharge, with some patients even using telemedicine. Results: Increased values of alpha-1 antitrypsin were detected in advanced stages of the disease, and a clear improvement of clinical and functional parameters was observed after inclusion in the rehabilitation program. Conclusions: Detection of alpha-1 antitrypsin deficiency (AATD) is rare. The majority of patients diagnosed with lung cancer in advanced stages showed increased values of alpha-1 antitrypsin, AAT being able to be used as a follow-up marker in response to oncological treatment. Respiratory rehabilitation benefits in pulmonary tuberculosis, lung cancer, COPD, and asthma, regardless of the form of the disease. An interdisciplinary approach is necessary for the optimal treatment and control of lung diseases.